Effects of transcranial alternating current stimulation on motor performance and motor learning for healthy individuals: A systematic review and meta-analysis - Hu, Kun; Wan, Ruihan; Liu, Ying; Niu, Maolin; Guo, Jianrui; Guo, Feng (Frontiers in Physiology, 2022)
Objective:Previous behavioral studies have reported the potential of transcranial alternating current stimulation in analyzing the causal relationship between neural activity and behavior. However, the efficacy of tACS on motor performance and learning in healthy individuals remains unclear. This systematic reviewexamines the effectiveness of tACS on motor performance and motor learning in healthy individuals. Methods: Literature was systematically searched through the Cochrane Library, PubMed, EMBASE, and Web of Science until 16 October 2022. Studies were eligible for review if they were randomized, parallel, or crossover experimental designs and reported the efficacy of tACS on motor performance and motor learning in healthy adults. Review Manager 5.3 was used to evaluate the methodological quality and analyze the combined effect. Results: Ten studies (270 participants) met all the inclusion criteria. The results showed that motor performance was not significantly greater than that with sham tACS stimulation [I2 = 44%, 95% CI (–0.01, 0.35), p = 0.06, standardized mean difference = 0.17], whereas motor learning ability improved significantly [I2 = 33%, 95% CI (−1.03, −0.31), p = 0.0002, SMD = −0.67]. Subgroup analysis found that gamma bend tACS could affect the changes in motor performance (I2 = 6%, 95% CI (0.05, 0.51), p = 0.02, SMD = 0.28), and online tACS did as well [I2 = 54%, 95% CI (0.12, 0.56), p = 0.002, SMD = 0.34]. Conclusion: The results showed that tACS effectively improves motor performance (gamma band and online mode) and motor learning in healthy individuals, which indicates that tACS may be a potential therapeutic tool to improve motor behavioral outcomes. However, further evidence is needed to support these promising results. Systematic Review Registration: PROSPERO, identifier CRD42022342884